Joyce's Ulysses : a reader's guide - Sheehan, Sean, 1951- (Continuum reader's guides., 2009)
Ulysses remains less widely read than most texts boasting such a canonical status, largely due to misunderstanding about how to read it, and this guide provides an easy to follow remedy. By showing how Joyce reacted to the historical and cultural context in which he was situated, the radical nature of his use of language is laid bare in a chapter-by-chapter analysis of Ulysses . This approach enables the student reader to read and enjoy the novel's plurality of styles and to understand the terms of critical debate surrounding the nature and significance of Joyce's novel.